Maternal plasma vitamin D levels across pregnancy are not associated with neonatal birthweight: findings from an Australian cohort study of low-risk pregnant women - Paige F. van der Pligt; Stacey J. Ellery; Deborah L. de Guingand; Gavin Abbott; Paul A. Della Gatta; Robin M. Daly (BMC Pregnancy and Childbirth, 2023)
Abstract Background In utero environments can be highly influential in contributing to the development of offspring obesity. Specifically, vitamin D deficiency during pregnancy is associated with adverse maternal and child health outcomes, however its relationship with offspring obesity remains unclear. We assessed maternal vitamin D status across pregnancy, change in plasma vitamin D concentrations and associations with neonatal birthweight, macrosomia and large for gestational age. Methods Women (n = 221) aged 18–40 years with singleton (low-risk) pregnancies, attending antenatal clinics at a tertiary-level maternity hospital were recruited at 10–20 weeks gestation. Medical history, maternal weight and blood samples at three antenatal clinic visits were assessed; early (15 ± 3 weeks), mid (27 ± 2 weeks) and late (36 ± 1 weeks) gestation. Maternal 25(OH)D was analysed from stored plasma samples via liquid chromatography-tandem mass spectrometry (LC/MS/MS). Neonatal growth parameters were collected at birth. Unadjusted and adjusted linear and logistic regression assessed associations of maternal vitamin D with birthweight, macrosomia and large for gestational age. Results Mean plasma 25(OH)D increased from early (83.8 ± 22.6 nmol/L) to mid (96.5 ± 28.9 nmol/L) and late (100.8 ± 30.8 nmol/L) gestation. Overall 98% of women were taking vitamin D-containing supplements throughout their pregnancy. Prevalence of vitamin D deficiency (25(OH)D < 50 nmol/L) was 6.5%, 6.3% and 6.8% at early, mid and late pregnancy respectively. No statistically significant association was found between 25(OH)D or vitamin D deficiency at any timepoint with neonatal birthweight, macrosomia or large for gestational age. Conclusions Prevalence of vitamin D deficiency was low in this cohort of pregnant women and likely related to the high proportion of women taking vitamin D supplements during pregnancy. Maternal 25(OH)D did not impact offspring birth weight or birth size. Future studies in high-risk pregnant populations are needed to further assess maternal vitamin D status and factors in utero which promote early life obesity.